Nanoscale modulation of electronic states across unit cell steps on the surface of an epitaxial colossal magnetoresistance manganite film - Rana, Abhimanyu; Bogle, Kashinath A.; Game, Onkar S.; Patil, Shankar; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2010)
The nature of electronic states near the edge of unit cell steps on the surface of epitaxial La(0.7)Sr(0.3)MnO(3) (LSMO) thin films grown by real-time reflection high energy electron diffraction monitored pulsed laser deposition is examined by scanning tunneling microscopy and scanning tunneling spectroscopy techniques. It is observed that the electronic states are strongly modulated near the step edge with considerably high gap at the edge and low gap on the terrace. This modulation weakens at low temperature. The temperature evolution of the density of states and the nature of gap in deep metallic state of LSMO are also discussed. (C) 2010 American Institute of Physics. [doi:10.1063/1.3455886]
Keywords: colossal magnetoresistance; electronic density of states; lanthanum compounds; magnetic epitaxial layers; Nanostructured materials; pulsed laser deposition; reflection high energy electron diffraction; scanning tunnelling microscopy; scanning tunnelling spectroscopy; strontium compounds

Growth of aligned ZnO nanorods array on ITO for dye sensitized solar cell - Yengantiwar, Ashish; Sharma, Ramakant; Game, Onkar S.; Banpurkar, Arun G. (Current Applied Physics, 2011)
Aligned ZnO films of nanorods arrays were grown on Indium doped Tin oxide (ITO) glass substrate for the Dye Sensitized Solar Cells (DSSCs) applications. Two-step approach was employed for the deposition, which offers advantages such as excellent surface adhesion, large area deposition, high reproducibility and yield. Structural characterization using X-ray diffraction (XRD) shows a preferred c-axis (002) oriented growth. Scanning Electron Microscopy (SEM) images reveals uniformly distributed hexagonal ZnO nanorods with average diameter varying from 80 to 250 nm. Average growth rate of the films was estimated using Surface Profilometer which was found to be similar to 1 mu m/h. Optical characterizations were carried out using Photo-spectrometer and Raman spectroscopy. The DSSCs using these ZnO films of nanorods array as photo-electrodes show conversion efficiency ranging from 0.24 to -0.71 %, the maximum efficiency was obtained for films deposited for time duration 8 h. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aligned ZnO nanorod growth; Dye sensitized solar cell; Open aqueous solution deposition

Shape preserving chemical transformation of ZnO mesostructures into anatase TiO2 mesostructures for optoelectronic applications - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Yengantiwar, Ashish; Ogale, Satishchandra B. (Energy & Environmental Science, 2011)
In this work we report on the synthesis of various ZnO mesostructures (rods, spheres, flakes and flower-like morphologies) by hydrothermal and co-precipitation methods and their remarkable and complete transformation into anatase TiO2 mesostructures with nominally similar shapes using controlled low temperature TiCl4 treatment. Various techniques are used to demonstrate the phase purity and morphology details. Based on the careful examination of the transformation of ZnO rods into TiO2 tubes we suggest a mechanism which embodies initial formation of a thin TiO2 shell on the ZnO surface by ion exchange (Ti4+-Zn2+) followed by Zn diffusion through the shell and its oxidation on the surface. We used these converted TiO2 mesostructures for light harvesting in Dye Sensitized Solar Cells (DSSCs) to enhance the conversion efficiency. It is shown that DSSCs made using a doctor bladed film of TiO2 nanoparticles with an overlayer of TiCl4 treated ZnO flowers yield a solar cell efficiency of 6.9% which is considerably higher than that with only TiO2 nanoparticle film (5.4%) of comparable thickness.

Strong photo-response in a flip-chip nanowire p-Cu2O/n-ZnO junction - Deo, Meenal S.; Mujawar, Sarfraj; Game, Onkar S.; Yengantiwar, Ashish; Banpurkar, Arun G.; Kulkarni, Sneha; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Nanoscale, 2011)
Cu2O nanoneedles are synthesized on a copper substrate by a simple anodization and reducing ambient annealing protocol. ZnO nanorods are grown on ITO coated glass by a low temperature chemical route. The electronic and photo-response properties of the p-Cu2O/n-ZnO flip-chip heterojunction are then studied and analyzed. We show that the I-V characteristic is rectifying and the junction exhibits a good photoresponse (similar to 120% under 1 V reverse bias) under AM 1.5 (1 Sun) illumination. This nano-heterojunction photo-response is far stronger as compared to that of a pulsed laser deposited thin film p-Cu2O/n-ZnO heterojunction, which can be attributed to higher junction area in the former case.

TiO2-Au plasmonic nanocomposite for enhanced dye-sensitized solar cell (DSSC) performance - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Vijayamohanan, K.; Bogle, Kashinath A.; Valanoor, N.; Ogale, Satishchandra B. (Solar Energy, 2012)
Anatase TiO2 nanoparticles dressed with gold nanoparticles were synthesized by hydrothermal process by using mixed precursor and controlled conditions. Diffused Reflectance Spectra (DRS) reveal that in addition to the expected TiO2 interband absorption below 360 nm gold surface plasmon feature occurs near 564 nm. It is shown that the dye sensitized solar cells made using TiO2-Au plasmonic nanocomposite yield superior performance with conversion efficiency (CE) of similar to 6% (no light harvesting), current density (J(SC)) of similar to 13.2 mA/cm(2), open circuit voltage (V-oc) of similar to 0.74 V and fill factor (FF) 0.61; considerably better than that with only TiO2 nanoparticles (CE similar to 5%, J(SC) similar to 12.6 mA/cm(2), V-oc similar to 0.70 V, FF similar to 0.56). (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Anatase TiO2; Au; Dye-sensitized solar cells; Hybrid composite; hydrothermal

Ferromagnetism in metal oxide systems: interfaces, dopants, and defects - Thakare, Vishal P.; Game, Onkar S.; Ogale, Satishchandra B. (Journal of Materials Chemistry C, 2013)
Ferromagnetism in metal oxide systems has always attracted scientific attention in view of the intriguing and interesting interplay of spin, charge, orbital and lattice degrees of freedom that such systems display. This trend appears to be continuing with enhanced focus on interface systems, multiferroics, diluted magnetic semiconducting oxides (DMSOs) and nanomaterial magnetism. Newer techniques are being applied to bring out materials issues that are critical to the precise understanding of the origin of magnetism in certain cases. Interest is also beginning to grow in exploring application potential of some such systems. In this article we review the developments in this field by late 2011 and 2012.

CH3NH3PbI(3-x)(BF4)(x): molecular ion substituted hybrid perovskite - Nagane, Satyawan; Bansode, Umesh P.; Game, Onkar S.; Chhatre, Shraddha; Ogale, Satishchandra (Chemical Communications, 2014)
A molecular ion (BF4-) substituted hybrid perovskite CH3NH3PbI(3-x)(BF4)(x) is synthesized. The substituted perovskite shows significant enhancement in electrical conductivity at low frequencies and improved photoresponse under AM1.5 illumination as compared to the perovskite (CH3NH3PbI3).

Enhanced catalytic activity of polyethylenedioxythiophene towards tri-iodide reduction in DSSCs via 1-dimensional alignment using hollow carbon nanofibers - Anothumakkool, Bihag; Game, Onkar S.; Bhange, Siddheshwar N.; Kumari, Tanya; Ogale, Satishchandra B.; Kurungot, Sreekumar (Nanoscale, 2014)
Here, we report a highly conducting 1-dimensionally (1-D) aligned polyethylenedioxythiophene (PEDOT) along the inner and outer surfaces of a hollow carbon nanofiber (CNF) and its application as a counter electrode in a dye sensitized solar cell (DSSC). The hybrid material (CP-25) displays a conversion efficiency of 7.16% compared to 7.30% for the standard Pt counter electrode, 4.48% for bulk PEDOT and 5.56% for CNF. The enhanced conversion efficiency of CP-25 is attributed to the accomplishment of high conductivity and surface area of PEDOT through the 1-D alignment compared to its bulk counterpart. Reduced charge transfer resistance and high conductivity of CP-25 could be proven by cyclic voltammetry, impedance analysis and Tafel experiments. Further, through a long-term stability test involving efficiency profiling for 20 days, it is observed that CP-25 possesses excellent durability compared to the bulk PEDOT.

Enhancing efficiency of perovskite solar cell via surface microstructuring: superior grain growth and light harvesting effect - Tathavadekar, Mukta C.; Agarkar, Shruti A.; Game, Onkar S.; Bansode, Umesh P.; Kulkarni, Sneha A.; Mhaisalkar, Subodh G.; Ogale, Satishchandra B. (Solar Energy, 2015)
We have introduced a novel approach to enhance the perovskite solar cell efficiency by controlling the grain growth and light harvesting properties of perovskite crystallites. Instead of using a mesoporous TiO2 layer, we have modified the surface microstructuring of the TiO2 film by dispensing nano assembled TiO2 submicron structures (nanobeads, NBs) on TiO2 compact layer. With this new approach solar cell efficiency was improved significantly through an increase in both J(sc) and V-oc. This high efficiency is attributed to crystallite size of the perovskite phase. These also act as light scattering centers giving higher current density and reduced recombination effects giving higher open circuit voltage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grain growth; Light harvesting; Perovskite solar cells; TiO2 nanobeads

Hybrid perovskite films by a new variant of pulsed excimer laser deposition: a room-temperature dry process - Bansode, Umesh P.; Naphade, Rounak; Game, Onkar S.; Agarkar, Shruti A.; Ogale, Satishchandra (Journal of Physical Chemistry C, 2015)
A new variant of the classic pulsed laser deposition (PLD) process is introduced as a room-temperature dry process for the growth and stoichiometry control of hybrid perovskite films through the use of nonstoichiometric single target ablation and off-axis growth. Mixed halide hybrid perovskite films nominally represented by CH(3)NH(3)PbI(3-x)A(x) (A = Cl or F) are also grown and are shown to reveal interesting trends in the optical properties and photoresponse. Growth of good quality lead-free CH3NH3SnI3 films is also demonstrated, and the corresponding optical properties are presented. Finally, perovskite solar cells fabricated at room temperature (which makes the process adaptable to flexible substrates) are shown to yield a conversion efficiency of about 7.7%.

Highly stable laser-scribed flexible planar microsupercapacitor using mushroom derived carbon electrodes - Yadav, Poonam; Basu, Aniruddha; Suryawanshi, Anil; Game, Onkar S.; Ogale, Satishchandra (Advanced Materials Interfaces, 2016)
A report is presented on the fabrication of all solid-state interdigitated flexible microsupercapacitor using ultrafast and highly scalable laser scribing technique, using highly mesoporous carbon synthesized from biomass (mushroom) with hydrothermal preprocessing. The specific protocol used for carbon synthesis renders some unique property features to the material (surface area of 2604 m(2) g(-1) with hierarchical pore size distribution) in the context of supercapacitor electrode application. A polyvinyl alcohol (PVA)-H2SO4 gel electrolyte is used for electrochemical measurements. The microsupercapacitor shows high cyclic stability up to 15000 cycles. Moreover it shows nearly 90% stability after 1000 bending cycles at 60 degrees angle. It also retains its performance even under 120 degrees bending condition. This work represents a facile and fast technique for microscaled device fabrication that can be easily commercialized. Moreover, the mushroom-derived carbon used to make the electrodes holds great promise in context of the stability and flexibility of flexible supercapacitors.

Pt- and TCO-free flexible cathode for DSSC from highly conducting and flexible PEDOT paper prepared via in situ interfacial polymerization - Anothumakkool, Bihag; Agrawal, Ishita; Bhange, Siddheshwar N.; Soni, Roby; Game, Onkar S.; Ogale, Satishchandra B.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
Here, we report the preparation of a flexible, free-standing, Pt- and TCO-free counter electrode in dye-sensitized solar cell (DSSC)-derived from polyethylenedioxythiophene (PEDOT)-impregnated cellulose paper. The synthetic strategy of making the thin flexible PEDOT paper is simple and scalable, which can be achieved via in situ polymerization all through a roll coating technique. The very low sheet resistance (4 Omega/square) obtained from a film of 40 mu m thick PEDOT paper (PEDOT-p-5) is found to be superior to the conventional fluorine-doped tin oxide (FTO) substrate. The high conductivity (357 S/cm) displayed by PEDOT-p-5 is observed to be stable under ambient conditions as well as flexible and bending conditions. With all of these features in place, we could develop an efficient Pt- and TCO-free flexible counter electrode from PEDOT-p-5 for DSSC applications. The catalytic activity toward the tri-iodide reduction of the flexible electrode is analyzed by adopting various electrochemical methodologies. PEDOT-p-5 is found to display higher exchange current density (7.12 mA/cm(2)) and low charge transfer resistance (4.6 Omega) compared to the benchmark Pt-coated FTO glass (2.40 mA/cm(2) and 9.4 Omega, respectively). Further, a DSSC fabricated using PEDOT-p-5 as the counter electrode displays a comparable efficiency of 6.1% relative to 6.9% delivered by a system based on Pt/FTO as the counter electrode.
Keywords: counter electrode; dye-sensitized solar cell; flexible and thin devices; impedance analysis; interfacial polymerization; polyethylenedioxythiophene